The Synchronization of Customary Practices and Sharia in the Marriage Traditions of the Banjar Community - Syamsiah Nur; Thoat Stiawan; Yusrial Yusrial; Alhusni Alhusni; Misranetti Misranetti (al-Rasῑkh: Jurnal Hukum Islam, 2026)
Marriage in Indonesian society is often not solely based on Islamic law but is also influenced by customary practices that have been passed down through generations. This raises questions regarding the extent to which such customs are aligned with the principles of Islamic law, particularly within the Banjar community in Tembilahan, Indragiri Hilir Regency. This study analyzes the synchronization between custom (adat) and Islamic law (sharia) in the marriage traditions of the Banjar community in Tembilahan. It examines how customary practices remain consistent with Islamic legal principles while also strengthening social relations and kinship ties (silaturahmi). This research employs a qualitative method with a descriptive-analytical approach, using interviews, observations, and documentation as data collection techniques. The findings indicate that the marriage traditions of the Banjar community do not contradict Islamic law; rather, they function as a form of ‘urf ṣaḥīḥ (valid custom), as long as they are based on mutual consent (antarāḍin), do not impose excessive financial burden, and do not contain prohibited elements such as polytheism (shirk) and extravagance. Practices such as jujuran reflect a social system rooted in cultural values while still maintaining legitimacy within the framework of Islamic law. Furthermore, the integration of custom and sharia demonstrates that Islamic law serves as the primary foundation for the validity of marriage, while custom enriches its social and philosophical dimensions. These findings are in line with the objectives of Maqāṣid al-Sharī‘ah, particularly in preserving lineage (ḥifẓ al-nasl) and honor (ḥifẓ al-‘irḍ). Overall, the marriage traditions of the Banjar community in Tembilahan reflect a comprehensive harmonization between custom and Islamic law within the framework of local Islamic wisdom.